Comprehensive acetyl-proteomic analysis of Cytospora mali provides insight into its response to the biocontrol agent Bacillus velezensis L-1 - Sun, Pingping; Ma, Qiang; Zhang, Lei (Frontiers in Sustainable Food Systems, 2022)
Cytospora mali is an important factor for apple valsa canker, and Bacillus veleznesis L-1 is an effective biocontrol agent against apple valsa canker. Quantitative acetyl-proteomics is known to regulate transcriptional activity in different organisms; limited knowledge is available for acetylation modification in C. mali, and its response to biocontrol agents. In this study, using Tandem Mass tag proteomic strategies, we identified 733 modification sites on 416 proteins in C. mali, functions of these proteins were analyzed using GO enrichment and KEGG pathway. Some lysine acetylated proteins are found to be important to the fungal pathogenicity of C. mali, and also the response of fungi to biostress. B. velezensis L-1 suppressed the C. mali QH2 by causing the energy shortage and reduced virulence. Correspondingly, the C. mali QH2 could alleviate the suppression of biostress by upregulation of autophagy, peroxidase, cytochrome P450, ABC transporter and Heat shock protein 70. In summary, our results provided the first lysine acetylome of C. mali and its response to B. velezensis L-1.